Farm-Level Agricultural Biodiversity in the Peruvian Andes Is Associated with Greater Odds of Women Achieving a Minimally Diverse and Micronutrient Adequate Diet - Jones, Andrew D.; Creed-Kanashiro, Hilary M.; Zimmerer, Karl S.; Haan, Stef de; Carrasco, Miluska; Meza, Krysty; Cruz García, Gisella S.; Tello, Milka; Amaya, Franklin Plasencia; Marin, R. Margot; Ganoza, Lizette (Elsevier, 2018)
Abstract Background